Arabic Linguistic Landscape as a Pedagogical Space in Bilingual Pesantren - Nasikul Mustofa Efendi; Kamal Yusuf; Nasaruddin; Muflihah; Muhammad Alfa Choirul Murtadho (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2026)
Linguistic Landscape (LL) studies examine the visibility of language in public spaces through signs, symbols, and written displays that shape social interaction and meaning-making. Although LL research has expanded considerably in educational contexts, limited scholarly attention has been directed toward the pedagogical functions of Arabic Linguistic Landscapes within pesantren as bilingual Islamic learning environments. This article delves into investigation on how Arabic linguistic signs operate not only as institutional markers but also as pedagogical resources in Pesantren Modern Al-Amanah Junwangi, Indonesia. Adopting a descriptive qualitative design, data were collected through observation and documentation of Arabic linguistic displays across the pesantren environment, including slogans, informational boards, directional signs, and other visual texts. The data were analyzed to identify the forms, distribution, and educational functions of Arabic signs within students’ everyday linguistic practices. The findings reveal that the Arabic Linguistic Landscape performs multiple interconnected roles: representing institutional identity, reinforcing language policy, and facilitating informal language acquisition beyond classroom settings. Continuous exposure to Arabic signage contributes to vocabulary development, habituates students to authentic linguistic expressions, and strengthens the implementation of language activities in daily interaction. More importantly, the study demonstrates that the integration of Arabic signs into the pesantren environment constructs an immersive and socially embedded language-learning ecology that bridges formal instruction and authentic communicative practice. By situating Arabic Linguistic Landscape as a pedagogical mediator within bilingual Islamic education, this study extends current LL scholarship beyond symbolic representation toward its role in sustaining environment-based language learning.